Denosumab combined with chemotherapy followed by anlotinib in the treatment of multiple metastases of malignant peripheral nerve sheath tumor: a case report and literature review - Chen, Qian; Cui, Haocheng; Zheng, Kai; Xu, Ming; Yu, Xiuchun (Frontiers in Oncology, 2024)
Primary intraosseous malignant peripheral nerve sheath tumors (MPNSTs) are rare yet highly aggressive neoplasms originating from peripheral nerves.Typically manifesting as soft tissue masses accompanied by pain or functional impairment, these tumors pose significant challenges in management. Surgical intervention remains the cornerstone of treatment for patients with MPNST lacking distant metastasis, with generally modest success rates. In cases of recurrence and metastasis, the pursuit of effective systemic therapies has been a focus of clinical investigation. Herein, we present a case study involving an elderly female patient with refractory MPNST. In light of surgical limitations, a multimodal therapeutic approach combining chemotherapy, denosumab, and subsequent administration of anlotinib was pursued following collaborative consultation. This regimen yielded noteworthy clinical benefits, exemplifying a promising avenue in the management of challenging MPNST cases.